Peran Kelembagaan Dalam Pengembangan Agribisnis Kubis (Brassica Oleracea) Pada Kelompok Tani Argoayuningtani Di Kabupaten Boyolali - Aprilliyanti, Eka; Suswadi; Arbianti; Prasetyo, Agung (JURNAL ILMIAH AGRINECA, 2024)
This study aims to find out what institutions play a role in the development of cabbage agribusiness, find out the level of institutional performance, and find out the level of satisfaction of farmers with the institutional performance of cabbage agribusiness in the Argoayuningtani Farmer Group, Senden Village, Selo District, Boyolali Regency. The method used is the purposive sampling method. The data analysis methods used are likert analysis, Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI). The results of the study show that the institutional performance of production facilities, marketing, farmer groups, financing, as well as information and technology is considered satisfactory and in accordance with farmers' expectations. The priority for improvement is in quadrant 1, namely the quality of saprodi and agricultural tools, information and price stability, the existence of cooperatives, and farmer groups as production units. The level of satisfaction of farmers with the institutional performance of cabbage agribusiness is included in the satisfied category.